Cooperative negawatt P2P energy trading for low-voltage distribution networks. (1st October 2021) - Azim, M. Imran; Tushar, Wayes; Saha, Tapan K.
Abstract: In this paper, the formation and feasibility of negawatt (nW) peer-to-peer (P2P) energy trading in a grid-connected energy network are studied. In particular, a framework is presented to introduce nW P2P trading concept in the local electricity market in order to provide cost savings to each participating prosumer. To capture the decision-making strategy of various nW prosumers, a coalition game model is proposed whereby prosumers can trade energy frequently in a collaborative way. The proposed nW P2P trading framework satisfies the beneficial criterion of the coalition game. Also, it confirms the stability and prosumer-focused feature of the structured coalition. To distribute the total coalition payoff between nW prosumers, Shapley value and Nucleolus are used. Finally, simulation results are provided to examine the effectiveness of the developed nW P2P trading on an actual distribution network. The simulation results emphasise that the proposed nW P2P trading can (1) enable prosumers to minimise notable portion of their electricity costs compared to the grid's-facilitated demand response scheme, (2) keep total power loss and voltage profiles within permissible ranges, and (3) avoid network protection arrangements required for voltage regulation as opposed to kilowatt P2P trading. Highlights: The application of peer-to-peer (P2P) negawatt (nW) trading at the distribution level is emphasised to reduce the electricity costs of the prosumers. A coalition game-based P2P nW trading framework is designed to study the decision-making behaviour of different prosumers. It is shown that the proposed P2P coalition is beneficial, stable, and prosumer-centric. A feasibility study of the proposed trading framework is carried out to inspect the physical performance. It is shown that the developed P2P nW trading does not have any detrimental impact on the network power losses and voltage profiles.